Clinical evidence of the nursing diagnosis Adult pressure injury* - Santos, Cássia Teixeira dos; Barbosa, Franciele Moreira; Almeida, Thayná de; Vidor, Isabella Duarte; Almeida, Miriam de Abreu; Lucena, Amália de Fátima (Revista da Escola de Enfermagem da USP, 2021)
Objective: To identify clinical evidence of the nursing diagnosis Adult pressure injury. Method: Cross-sectional study with 138 adult patients, with community-acquired or hospital-acquired pressure injuries, admitted to clinical, surgical, and intensive care units. Data collected from Electronic health records (EHR) and from the clinical assessment of patients at the bedside, analyzed through descriptive statistics. Results: The partial thickness loss of dermis presenting as a shallow open ulcer, intact or open/ruptured blister, consistent with a stage II pressure injury, was the significant defining characteristic. Significant related factors were pressure on bony prominence, friction surface, shear forces, and incontinence. The population at significant risk was that at age extremes (≥60 years). Significant associated conditions were pharmacological agent, physical immobilization, anemia, decreased tissue perfusion, and impaired circulation. Conclusion: The clinical indicators assessed in the patients showed evidence of the nursing diagnosis Adult pressure Injury, with significant lesions consistent with stage II, resulting from pressure, especially in elderly individuals, and in those on various medications.